Effects of chrononutrition on aging and lifespan - Yiming Wang; Siyu Zhang; Ping Xiang; Gaoyu Liu; Aiman Yu; Hanxi Yuan; Linli Jiang; Dan Shi (Food Research International, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Efficient activating peracetic acid by copper-aluminum composites to degrade sulfathiazole: The critical role of Cu(III) species - Yuxiao Mu; Yanping Ding; Linli Tan; Qiulin Shi; Lei Chen; Jiaqi Ding; Jingwen Wang; Yong Liu; Pengchao Xie (Journal of Environmental Chemical Engineering, 2025)

Correction: Testing the validity of the Montgomery–Koyama–Smith equation and the power law equation using 3231 tepals of a Magnolia species - Linli Deng; Jinfeng Wang; Li Zhang; Dirk Hölscher; Peijian Shi (Trees, 2025)

Corrigendum to “Development of downscaling technology for land surface temperature: A case study of Shanghai, China” [Urban Climate 61 (2025) 102412] - Shitao Song; Jun Shi; Dongli Fan; Linli Cui; Hequn Yang (Urban Climate, 2025)

Testing the validity of the Montgomery–Koyama–Smith equation and the power law equation using 3231 tepals of a Magnolia species - Linli Deng; Jinfeng Wang; Li Zhang; Dirk Hölscher; Peijian Shi (Trees, 2025)
Key message The power-law equation provides marginally better accuracy than the Montgomery–Koyama–Smith equation for estimating total tepal area, with flexible definitions of maximum tepal length maintaining prediction reliability. Abstract Montgomery–Koyama–Smith equation (MKSE) and power law equation (PLE) were evaluated for estimating the total tepal area ( A T ) of Magnolia × soulangeana flowers using 3231 tepals from 359 flowers. MKSE assumes an isometric relationship between the A T and the product of summed tepal widths ( L KS ) and maximum tepal length ( W KS ), while PLE incorporates an allometric scaling exponent (α). Results showed α = 0.9561 (95% CI 0.9481–0.9641), confirming allometry. PLE exhibited slightly lower root-mean-square error (RMSE: 0.0149 vs. 0.0172) and mean absolute percentage error (MAPE: 1.18% vs. 1.35%) than MKSE. Redefining W KS as a random selection from the largest 9, 6, or 3 tepal lengths per flower minimally affected model performance, with MAPE consistently below 5% even when sampling the entire length range. This flexibility simplifies field measurements without compromising accuracy. Variability in geometric series common ratios across flowers likely drives the observed allometric scaling. This study validates that A T can be reliably estimated using summed widths and a flexibly defined maximum length, emphasizing PLE’s marginally superior fit. These findings advance methods for non-destructive floral trait quantification in species with fixed organ counts.

Development of downscaling technology for land surface temperature: A case study of Shanghai, China - Shitao Song; Jun Shi; Dongli Fan; Linli Cui; Hequn Yang (Urban Climate, 2025)

Based on the resting-state functional magnetic resonance imaging reveals the causal relationship between the brain function network and the risk of tinnitus: a bidirectional Mendelian randomization analysis - Yuchao Liu; Chunli Li; Linli Yao; Yuan Tan; Lu Shi; Pei Chen (Brain Imaging and Behavior, 2025)

HRD1 reduction promotes cholesterol-induced vascular smooth muscle cell phenotypic change via endoplasmic reticulum stress - Linli Wang; Zhitao Ren; Lin Wu; Ximei Zhang; Min Wang; Haiming Niu; Xuemin He; Heting Wang; Yanming Chen; Guojun Shi; Xiaoxian Qian (Molecular and Cellular Biochemistry, 2024)

Ciprofloxacin Accelerates Angiotensin-II-Induced Vascular Smooth Muscle Cells Senescence Through Modulating AMPK/ROS pathway in Aortic Aneurysm and Dissection - Weiyue Zeng; Yaowen Liang; Shangjun Huang; Jiarui Zhang; Cong Mai; Binbin He; Linli Shi; Baojuan Liu; Weifeng Li; Xiaoran Huang; Xin Li (Cardiovascular Toxicology, 2024)

Evaluation and Application of Fengyun-4A/LMI Data in Tropical Cyclone Monitoring Over the Southeast Coast of China - Linli Cui; Jun Shi; Wei Guo; Yinglong Xu; Yiwen Lu (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Exosomal miR-486-5p derived from human placental microvascular endothelial cells regulates proliferation and invasion of trophoblasts via targeting IGF1 - Ruixia Ma; Zhijiang Liang; Xiaomei Shi; Linli Xu; Xiaowei Li; Jinhua Wu; Lina Zhao; Guocheng Liu (Human Cell, 2021)
Preeclampsia (PE) is a serious complication of pregnancy. Exosomes are known to be upregulated in PE. In this study, we sought to investigate the effect of miR-486-5p from human placental microvascular endothelial cells, on the function of trophoblast cells. To investigate the function of human placental microvascular endothelial cell (HPVEC)-derived exosomes on trophoblast cells, HPVECs were treated with hypoxia/reoxygenation (H/R). The separation efficiency of exosomes was determined by transmission electron microscopy, nanosight and Western blot. Cell Counting Kit-8, EdU staining, wound-healing, and transwell assay were performed to detect the effect of exosomally transferred miR-486-5p inhibitor on proliferation, migration and invasion of trophoblast cells. MiRDB and dual-luciferase report assay were used to find the target of miR-486-5p. Our data revealed that miR-486-5p was significantly upregulated in H/R-treated HPVEC-Exo, and miR-486-5p was enriched in HPVEC-Exo. miR-486-5p inhibitor carried by HPVEC-Exo significantly inhibited the proliferation, migration and invasion of trophoblast cells. Insulin-like growth factor 1 (IGF1) was found to be the target of miR-486-5p, and IGF1 overexpression notably reversed the effect of miR-486-5p inhibitor from HPVEC-Exo on trophoblast cell function. In summary, H/R-treated HPVEC-derived exosomally expressing miR-486-5p inhibitor significantly inhibited the proliferation, migration and invasion of trophoblast cells via downregulation of IGF1. The findings from the present study may be useful in the development of treatments for PE.

Temporal and spatial variations of high-impact weather events in China during 1959–2014 - Jun Shi; Kangmin Wen; Linli Cui (Theoretical and Applied Climatology, 2017)

Distribution and trend on consecutive days of severe weathers in China during 1959–2014 - Jun Shi; Kangmin Wen; Linli Cui (Journal of Geographical Sciences, 2016)

Relationship between parental genetic distance and offspring’s heterosis for early growth traits in Liriodendron: implication for parent pair selection in cross breeding - Junxiu Yao; Huogen Li; Jing Ye; Linli Shi (New Forests, 2016)

Urban transformation of a metropolis and its environmental impacts - Zhan Tian; Guiying Cao; Jun Shi; Ian McCallum; Linli Cui; Dongli Fan; Xinhu Li (Environmental Science and Pollution Research, 2012)

Characteristics of high impact weather and meteorological disaster in Shanghai, China - Jun Shi; Linli Cui (Natural Hazards, 2012)

Temporal and spatial response of vegetation NDVI to temperature and precipitation in eastern China - Linli Cui; Jun Shi (Journal of Geographical Sciences, 2010)

Climatic characteristics of high temperature in East China during 1961–2005 - Jun Shi; Xu Tang; Linli Cui (Journal of Geographical Sciences, 2008)